Adhesion promoters - organo - silanes as pre - treatment of substrates surface / Mohamad Kamal Harun - Harun, Mohamad Kamal (Universiti Teknologi MARA Cawangan Pahang, 2000)
The principle behind adhesion promoters is the enhancement of the interfacial bond strength either by reacting chemically with both the phases or/and by altering the ctitical surface tension. These promoters which are sometimes referred to as coupling agents, form molecular bridges by reacting with free radicals and atoms between the inorganic substrate/s surface and the organic polymer matrix at the interface. These reactions can be easily achieved by selecting coupling agents bearing functional groups that can react with the polymer and the substrate. Organosilances are among the oldest adhesion promoters known and has been subjected to much study. This paper intends to introduce and discuss much of the findings and theories that has been put forward on the mechanisms of adhesion enhancement by organosilane compounds.